Comparison of the Mismatch Repair System between Primary and Metastatic Colorectal Cancers Using Immunohistochemistry - Jiyoon Jung; Youngjin Kang; Yoo Jin Lee; Eojin Kim; Bokyung Ahn; Eunjung Lee; Joo Young Kim; Jeong Hyeon Lee; Youngseok Lee; Chul Hwan Kim; Yang-Seok Chae (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Colorectal cancer (CRC) is one of the most common malignancies worldwide. Approximately 10%-15% of the CRC cases have defective DNA mismatch repair (MMR) genes. Although the high level of microsatellite instability status is a predictor of favorable outcome in primary CRC, little is known about its frequency and importance in secondary CRC. Immunohistochemical staining (IHC) for MMR proteins (e.g., MLH1, MSH2, MSH6, and PMS2) has emerged as a useful technique to complement polymerase chain reaction (PCR) analyses. Methods In this study, comparison between the MMR system of primary CRCs and paired liver and lung metastatic lesions was done using IHC and the correlation with clinical outcomes was also examined. Results Based on IHC, 7/61 primary tumors (11.4%) showed deficient MMR systems, while 13/61 secondary tumors (21.3%) showed deficiencies. In total, 44 cases showed proficient expression in both the primary and metastatic lesions. Three cases showed deficiencies in both the primary and paired metastatic lesions. In 10 cases, proficient expression was found only in the primary lesions, and not in the corresponding metastatic lesions. In four cases, proficient expression was detected in the secondary tumor, but not in the primary tumor. Conclusions Although each IHC result and the likely defective genes were not exactly matched between the primary and the metastatic tumors, identical results for primary and metastatic lesions were obtained in 77% of the cases (47/61). These data are in agreement with the previous microsatellite detection studies that used PCR and IHC.